2004
DOI: 10.5194/npg-11-631-2004
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in nonlinear kinetic Alfvén waves

Abstract: Abstract. This paper presents a review of recent progress in nonlinear kinetic Alfvén wave (KAW hereafter). We start with the two-fluid theory of KAWs and show how the difference between the motions of electrons and ions in smallscale fields of KAWs modifies the Alfvén wave properties. Then, we focus on nonlinear solitary structures of KAWs. A general criterion of the existence for solitary KAW (SKAW hereafter) and its exact analytical solution in a low-β plasma (β Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 69 publications
0
36
0
Order By: Relevance
“…In particular, it has been widely accepted that the dispersive small-scale MHD waves could be responsible for the dissipation of wave energies, as well as particle acceleration and plasma heating, which occur continually in various eruptive phenomena from terrestrial aurora and solar flares, to cosmic rays. The dispersive small-scale Alfvén wave, called KAW, has been extensively investigated and applied to plasma energization processes [1][2][3][4]. In analogous works, however, little attention has been paid to the fast and slow modes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, it has been widely accepted that the dispersive small-scale MHD waves could be responsible for the dissipation of wave energies, as well as particle acceleration and plasma heating, which occur continually in various eruptive phenomena from terrestrial aurora and solar flares, to cosmic rays. The dispersive small-scale Alfvén wave, called KAW, has been extensively investigated and applied to plasma energization processes [1][2][3][4]. In analogous works, however, little attention has been paid to the fast and slow modes.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the Alfvén wave, the dispersive wave is called the kinetic Alfvén wave (KAW). In the KAW, the perturbed electric fields have a non-zero component parallel to the background magnetic field that may cause efficient heating and acceleration of the plasma particles [1][2][3][4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have shown that the kinetic Alfvén waves are accompanied by spikes in the electric field directed both parallel and perpendicular to the ambient magnetic field and associated decreases in plasma density with n/n∼50% and transverse scales of the order of ∼c/ω pe (Louarn et al, 1994;Chaston et al, 1999;Genot et al, 1999;Wu and Chao, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…waves are associated with instabilities in regions where fieldaligned currents vary strongly across the field lines (Kozlovsky and Lyatsky, 1997; Wu and Seyler, 2003), and have been studied intensively, both experimentally and theoretically (Louarn et al, 1994;Carlson et al, 1998;Chaston et al, 1999Chaston et al, , 2003Chaston et al, , 2004Stasiewicz et al, 2000;Wygant et al, 2000;Paschmann et al, 2002;Wu and Chao, 2004). These studies have shown that the kinetic Alfvén waves are accompanied by spikes in the electric field directed both parallel and perpendicular to the ambient magnetic field and associated decreases in plasma density with n/n∼50% and transverse scales of the order of ∼c/ω pe (Louarn et al, 1994;Chaston et al, 1999;Genot et al, 1999;Wu and Chao, 2004).…”
Section: Introductionmentioning
confidence: 99%